Introduction to Hospitality - Walker, John R., 1944- (Harlow, England : Pearson, 2021)
"Introduction to Hospitality is a lively, comprehensive survey of the world's largest industry - hospitality. Students explore the vibrant inner workings of each hospitality segment, including hospitality and lodging; beverages, restaurants, and managed services; tourism, recreation, attractions, clubs, and gaming; assemblies, events, and attractions; and managerial areas of the hospitality industry. The 8th Edition highlights a range of issues shaping the future of each segment of the hospitality industry."--
Featuring contributions from industry experts, 'Introduction to Hospitality' profiles corporations and hospitality professionals, placing an emphasis on globalisation and environmental responsibility.
Part I: Introducing hospitality and lodging -- Part II: Beverages, restaurants and managed services -- Part III: Tourism, recreation, attractions, clubs, and gaming -- Part IV: Assemblies, events, attractions, leadership, and management -- Part V: Managerial areas of the hospitality industry.
Authorized adaptation of the eighth United States edition published in 2020. ISBN: 9780135209813.
Includes glossary.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Hospitality industry -- Management -- Textbooks; Hospitality -- Management -- Textbooks; Hospitalité -- Gestion; Hospitality industry